The Subject of Theatre in the Lithuanian School: Relationships within the General Educational Cultural Context - Kazragytė, Vida (Pedagogika, 2013)
The article investigates the rather new educational phenomenon – about twenty years ago under the impact of educational reform the theatre subject teaching was introduced. In many neighbor’s countries there is no such separate theatre subject still yet. The focus of the article is on the relationships between the curricula of theatre subject (2008, 2001) and the practice of long-lived non-formal education of children and youth of Lithuania. The curricula of theatre subject were prepared according to comprehensive discipline-arts education conception formed in United States of Amerika. Taking into account the notion of M. Lukšienė, that experience of other cultures, as well as the educational innovations must be adopted according to “own cultural model”, the attention is paid to analysis how curricula of theatre subject are grounded on traditions of Lithuanian non-formal education, especially its artistic trend. The self-expression paradigm or psychological trend of theatre education is less evident in our context. The roots of artistic trend are in Jesuit’s school theatre that existed in Lithuania 1570–1843. The artistic trend was recreated at the end of 20th century in non-formal theatre education in Lithuania by relaying on the professional theatre pedagogy (the training of professional theatre pedagogues started, the first books of methodology of theatre education appeared). Analysis showed that common concepts, as “theatre” and “education through theatre” are those which relate artistic trend of non-formal theatre education with curricula of theatre subject, accordingly, which are grounded on discipline-based art education conception. Especially that is clear from the revealing of content of “education through theatre” concept and explaining its formative and cognitive impacts on children and youth who are acting the roles created by dramaturge. The biggest challenge related with coming of theatre subject as separate, is the creating of theatre knowledge appropriated for school children. Now the theatre subject curricula describe the knowledge which are known in professional theatre pedagogy and in artistic trend of non-formal theatre education, but only in part. Thy must be expanded by new knowledge which will be get by way of externalization from direct practice. Also, there is a need of artistic orientation of theatre didactics – that can guarantee the succession of the best traditions of Lithuanian‘s theatre education and encourage their development.